PENCANTUMAN HARGA DALAM IKLAN PADA SURAT KABAR - Salim Salim (Canthing, 2012)
In effect the company aims to satisfy consumers, in addition to gain or profit. Advertising as part of promotional activities in the promotion of media communication needs. One newspaper section of the print communications media. Thus the idea or ideas in advertising can be delivered through the medium of communication. Good advertising is advertising that can persuade consumers to buy products or use the services offered. Inclusion in the price of advertising can bring great benefits to the marketing of products and services. Psychological aspects of pricing could provide a powerful influence on consumers to make purchases.